Barisan Nasional (BN) Hegemony in P188 Silam: analysis from GE11 to GE14 - Nordin Sakke; Ramli Dollah; Wan Shawaluddin Wan Hassan; Fadilah Sarbi; Adi Jafar (2018)
The BN Hegemony of Silam, including Sabah started when UMNO succeeded to spread its wings to Sabah in 1994.The climax of Sabah hegemony happened when it was able to save BN from drowning during the political tsunami that was detected since 2004. However, issues related to the increasing cost of living, unemployment among young people, the problem of kleptocracy among politicians and the explosion of social media have changed the political landscape and witnessed the collapse of BN hegemony in GE14. Thus, this paper reviews the success of BN in maintaining its hegemony in Silam and how this hegemony was put to an end by non-BN parties especially Warisan. To explore this case, election results and press releases beginning GE-11 were analyzed. In addition, field surveys were conducted to confirm and strengthen the findings. The results of the analysis show that the factors maintaining BN's hegemony prior to GE-14 were heavily influenced by the national factor and the strength of BN’s machinery, as well as government agents who were successful in promoting a good impression of BN. However, during GE-14 BN failed to secure victory at P.188 Silam including the three state constituencies in N.49 Tungku, N.50 Lahad Datu and N.51 Kunak.The reason of this failure is due to anti-BN social media that managed to give negative perceptions of the issues faced by the government, resulting in a change of attitude in people, especially young voters in channels 3, 4 and 5.